Palmitic acid alone or combined with stearic and oleic enhances ruminal fiber degradation and alters microbiome composition - Batistel, Fernanda; Gonzalez, Osvaldo; Sears, Austin; Khan, Sharif Uddin; de Souza, Jonas (Frontiers in Microbiology, 2025)
IntroductionImproving ruminal fiber degradation is a key focus for enhancing animal performance and reducing the environmental impact of ruminant production systems. While dietary fat is typically recognized for impairing ruminal fiber degradation, recent research suggests that specific fatty acids, such as palmitic, stearic, and oleic, may have the potential to improve it. Since palmitic, stearic, and oleic are major components of the membranes of ruminal mixed bacteria, we hypothesize that supplying these fatty acids in proportions that mimic bacterial composition will promote microbial flow and, consequently, improve fiber degradation.MethodsDiets were randomly assigned to 8 single-flow continuous culture fermenters arranged in a replicated 4 × 4 Latin square with 6 days of adaptation and 4 days of sampling. Treatments were: (1) a basal diet without supplemental fatty acids (CON); (2) the basal diet plus 1.5% of palmitic acid (PA); (3) the basal diet plus 1.41% of stearic acid and 0.09% of oleic acid (SO); and (4) the basal diet plus 0.48% of palmitic acid, 0.95% of stearic acid, and 0.075% of oleic acid (PSO). Data were analyzed using a mixed model considering treatment as a fixed effect, and period and fermenter as random effects.Results and discussionBoth PA and PSO diets improved fiber degradation, increased the flow of short-chain fatty acids, and tended to increase microbial flow compared to the other treatments. Although the supply of dietary fatty acids did not change the total lipid content, they did alter the membrane fatty acid profile. For example, PA and PSO increased the concentration of specific fatty acids, such as anteiso C15:0, in the bacterial cell membranes, while SO and PSO reduced unsaturated fatty acids compared to PA and CON. Additionally, PA and PSO diets influenced the bacterial community, increasing populations of Fibrobacter and Prevotella while reducing Ruminococcus and Butyrivibrio. Our results indicate that including palmitic acid or a combination of palmitic, stearic, and oleic acids in proportions resembling those found in ruminal mixed bacteria improved ruminal fiber degradation, likely by partially modulating the rumen bacterial community composition.